Constructing a Conceptual Electronic Record Management System Model Based on Eight Indonesian Education Standards to Support School Accountability - Nina Oktarina; Murwatiningsih; Hana Netti Purasani; Ahmad Sehabuddin; Edy Suryanto (Journal of Information Science Theory and Practice, 2023)
Record management, especially in schools as an institution’s information centre, needs serious attention from government agencies. Under record management policy, there needs to be practical guidance on record management specific to schools. This paper aims to construct a record management model based on the Eight Indonesian Education Standards to support school accountability in Indonesia. The urgency of this paper in filling the gap in the Electronic Record Management System (ERMS) role is primarily to support school accountability. It is important to include educational laws and regulations in Indonesia to be a foundation in archive management, including preparing the ERMS. This study aims to develop a model of record management in schools. The final stage in this research is to find the final model. The final model is a model that experts and practitioners have validated. A total of 30 records managers were selected for the interviews. Furthermore, the trial was carried out in 30 senior high schools. The research sampling consisted of representatives of archive managers at selected schools from five islands in Indonesia (Kalimantan, Java, Papua, Sumatra, and Sulawesi). Our research findings show that conceptual models meet valid criteria and significantly impact archivist performance in better schools. The practical implication is that the archival management model based on national education standards policies contributes to practical archives and records management to support school accountability.